Exploring interprofessional education for collaborative practice in oral health education: a scoping review. - Van Dam, Lindsay; Rock, Leigha D.; Price, Sheri L. (Canadian Journal of Dental Hygiene, 2025)
Background: Interprofessional collaboration supports improved patient care and outcomes. Interprofessional education for collaborative practice (IPECP) in prelicensure education promotes professional/interprofessional socialization. Within IPECP, students gain understanding of their professional role and begin developing an interprofessional identity, including collaborative skills, attitudes, and behaviours. IPECP literature in oral health education is limited. It is not well understood how oral health students are involved in IPECP and prepared for collaborative practice. Objective: To assess the literature on IPECP within oral health education and identify IPECP models and characteristics of experiences enabling professional/interprofessional socialization, interprofessional identity development, and readiness for collaborative practice. Methods: Guided by JBI methodology, the research team searched CINAHL, DOSS, MEDLINE, and APAPsycInfo for peer-reviewed articles on IPECP models in prelicensure education of oral health students. Articles (N = 321) were screened by 2 reviewers for title/abstract, followed by full text. Twenty-eight articles were included. Results: Single and multiformat IPECP models were identified including workshops, case studies, simulation, and clinical experiences. Characteristics of IPECP experiences were identified and categorized as:1) learning from and about others; 2) establishing social connections; 3) authenticity of experiences; and 4) consistent socialization and exposure. However, challenges for IPECP in oral health education persist, including siloed education and a lack of intentional IPECP curriculum. Conclusion: Increased integration of oral health students into health professions IPECP and consistent exposure throughout programs is needed. IPECP curriculum must enable all students to explore their professional contributions to interprofessional teams. IPECP for developing an interprofessional identity in oral health students remains understudied; longitudinal and qualitative analyses are needed.